SRT606 : Research methodology in sport and behavioural science / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2020)
This course introduces students to the research processes in the field of sports sciences, sports management, recreation and leisure. Students will be exposed to various research methods including qualitative, quantitative, survey and experimental methods. They will be guided in data collection procedure and methods of sampling as well as data analysis. The course will also guide student in applying format and principles to prepare their research proposal and research report.